Toxicity and residual effects of toxic baits with spinosyns on the South American fruit fly - Schutze, Inana Xavier; Baronio, Cléber Antônio; Baldin, Morgana Mattiello; Loeck, Alci Enimar; Botton, Marcos (Pesquisa Agropecuaria Brasileira, 2018)
The objective of this work was to assess the lethal concentration and lethal time (LC and LT) of spinosad and spinetoram, combined with different food lures, and their residual effects on South American fruit fly (Anastrepha fraterculus). The toxic baits were offered in eight concentrations (2, 6, 14, 35, 84, 204, 495, and 1,200 mg L-1), combined with the following food lures: 7% sugarcane molasses, 3% Biofruit, 1.5% CeraTrap, 1.25% Flyral, 3% Samaritá Bait, and 3% Samaritá Tradicional; diluted food lures in water were used as controls. The residual effect of the formulations at 96 mg L-1 concentration were evaluated for 21 days and were compared with that of the commercial bait Success 0.02 CB. Both insecticides were toxic to adults of A. fraterculus, and mortality varied with the food lure used. The LC50 and LT50 ranged from 15.19 to 318.86 mg L-1 and from 11.43 to 85.93 hours, respectively. Spinosad was 2 to 36 times as toxic as spinetoram when combined with different hydrolyzed proteins. Toxic baits formulated with spinosad and spinetoram (96 mg L-1) caused mortality equivalent to the one by Success 0.02 CB (90.2%), when assessed on the day of application. Toxic baits formulated with 3% Biofruit + spinosad and 3% Samaritá Bait + spinetoram are effective for managing A. fraterculus and provide up to seven days of residual effect in the absence of rain; however, only Success 0.02 CB caused more than 80% mortality for up to 21 days.<!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->